Pengaruh Board System dan Board Composition terhadap Kinerja Perusahaan: Tinjauan terhadap Konsep Agency Theory dan Stewardship Theory dalam Corporate Governonce - Elok Pakaryaningsih; Yohan Sigit Wibowo (Jurnal Riset Manajemen dan Bisnis, 2006)
This research examines the effect of internal control mechanism of corporate governance that is board system and board composition on firm performonce. To be specific this research will be qualitatively analized to grasp the application of corporate governance tlteories, which are; agency and stewardship theory that underlie the implementation of corporate governance practices in Indonesian companies. The 198 samples are gathered from Indonesian companies listed in the Jakarta Stock Exchange during 1996 until 2003.Using the multiple linear regression method, board system that is represented by the level of blockholder shows it signtficant effect on firm performance. Wrhile the board size which stand for board composition also shows the similar effect. Furthermore the result of the analysis failed to notice which one of corporate governance theories that underlies the effectiveness of corporate governance practices on firm pedormance in Indonesia.Keywords: board system, board composition, board size, blockholder,pedormance